Faculty Members' Experiences of the Challenges and Facilitators of the Student Academic Guidance and Academic Counseling Process: A Qualitative Study - Forouzan Rezapur-Shahkolai; nooshin salimi; parisa parsa; Khadije Ezzati Rastgar; Elham Gheysvandi; mitra dogonchi (Kerman University of Medical Sciences, 2022)
Introduction: Academic guidance and counseling, while providing insights into the right decision-making methods and how to deal with life events, can increase the efficiency of the educational system and reduce academic failure. Given the importance of having in-depth knowledge of faculty members' opinions about counseling for evidence-based promotion, this study aimed to explore the challenges and facilitators of the academic counseling process.Methods: This qualitative study was conducted using Conventional content analysis to provide in-depth knowledge of the views of faculty members about the challenges and facilitators of the academic counseling process. The participants in this study were 24 faculty members from different schools of Hamadan University of Medical Sciences. They were selected through purposive sampling with maximum variation. The data were collected through semi-structured interviews with the participants.Results: The analysis of the data showed that the challenges and facilitators of the academic counseling process fall under six main themes, eight main categories, and eleven subcategories. The main themes that emerged in this study concerning the challenges of the academic counselling process were the organizational need to improve the conditions of academic counseling, the counselor's poor communication skills, and the student's failure to refer for counseling. Furthermore, the three main themes regarding the facilitators of the consulting process were the correct administration of the counseling curriculum, improving the counseling skills of the faculty members, and the separation of the counselor's role from the instructor's role.Conclusion: The consultation process at the university needs to be improved both in quality and in quantity. Therefore, empowering and equipping the consultant faculty members with adequate knowledge, attitudes, and skills through conducting effective training courses and workshops, and organizing briefing sessions to adjust students' expectations of the counseling faculty members, seem to be necessary for the consultation process improvement.